Persepsi (Tidak) Etis Mahasiswa Akuntansi: Ditinjau dari Pengetahuan Etika, Religiusitas dan Love of Money - Elsya Panduwinasari; Kurnia Ekasari; Kartika Susilowati (AKUNSIKA: Jurnal Akuntansi dan Keuangan, 2021)
The purpose of this study is to examine the influence of ethical knowledge, religiosity and love of money on the unethical perceptions of accounting students both partially and simultaneously. Respondents in this study were active students majoring in accounting at State Polytechnic of Malang. The sampling technique used purposive sampling with a sample size of 210 respondents. The data collection method uses a questionnaire containing 72 questions related to ethical knowledge, religiosity, love of money and unethical perception. The results of the study prove that the ethical knowledge has a significant and negative effect on the unethical perception of accounting students. The level of religiosity does not have a significant and positive effect on the unethical perception of accounting students. And also the love of money has a significant and positive effect on the unethical perception of accounting students. Simultaneously the ethical knowledge, religiosity, love of money have a significant effect on the unethical perception of accounting students.